Cholangitis Secondary to Lemmel Syndrome: Case Report - Nestor Apaez Araujo (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
Background: Acute cholangitis is a life threatening condition with multiple possible origins; one of this is the distal intermittent obstruction of biliary three by a duodenum yuxtapapillar diverticulum, an infrequent condition known as Lemmel syndrome. Case: An 83-year-old man come to emergency room complaining for intense abdominal pain and fever. Pathological background included cholecystectomy 4 years ago and right inguinal hernia repair 2 years before. He presents with epigastric, moderate intensity pain 4 days before, developing general discomfort, anorexia, asthenia, adinamia and nausea. Last 24 hours presents fever of 39.5º and jaundice. At physical exam with Glasgow 12, jaundice, dehydrated, tachycardia of 95 beats per minute, tachypnea 25 breaths per minute, abdominal pain located in epigastrium and right hypochondria, Murphy +, extremities with delayed capillary fulfi ll. Laboratories report hemoglobin 14.7 mg/dL, leucocytes 22000, neutrophils 95%, platelets 18500, total bilirubin 17 mg/dL, direct bilirubin 13.2 mg/dL. Ultrasound reports gallbladder absence, with intrahepatic biliary ducts dilated 7mm, and common bile duct 9 mm without intraluminal content. Medical treatment including metronidazole plus imipenem were initiated with good results and cholangitis resolution. ERCP was performed and this study reports a yuxtapapillar diverticulum type 1, a sphincterotomy was completed with clear biliary liquid evacuated and with posterior 10 French x 10 cm endoprothesis placement. Two days after that the patient was discharged but after one week he returned by mild cholangitis. Colangio-pancreatic magnetic resonance report similar fi ndings that in ERCP, with yuxtapapillar duodenal diverticulum. By clinical presentation and evolution Lemmel syndrome was diagnosed and conservative management with ERCP and sphincterotomy completed by the good outcomes, with patient discharge uneventfully 4 days later. Conclusions: The intermittent obstruction of biliary three by a duodenal diverticulum is a rare condition that must be suspected in cases of repetitive cholangitis and no evidence of choledocholithyasis, confi rmed by ERCP and discarding another anatomical abnormality by magnetic colangio-pancreatic magnetic resonance.